LEARNING INNOVATION IN THE DIGITAL ERA: INTEGRATING TECHNOLOGY IN THE CLASSROOM TO IMPROVE THE QUALITY OF EDUCATION - Mansori; Imas Siti Saidah; Bayu Grendo Sigarete (International Journal of Teaching and Learning, 2025)
Learning innovation in the digital era has become an important topic in educational discussions. Regarding the integration of technology in the classroom, this research aims to examine how technology can be used to improve the quality of education. In this information era, the use of digital tools in learning is not only a trend but also a necessity to support students in understanding complex concepts in various scientific disciplines. Through an extensive literature review of recent research, this study investigates various technological strategies and tools integrated into the classroom environment, including the use of educational applications, online learning platforms, educational games, and virtual reality. Next, this research examines the impact of the use of such technology on students' academic engagement and achievement, as well as how it helps in meeting different learning needs. The research results show that effective integration of technology into the learning process can make learning more interactive, increase student participation, and provide a more personalized and intellectually challenging learning experience. In conclusion, learning innovation in the digital era, through good technology integration, has significant potential to change education, making it more relevant to future needs and challenges.